Surat Perintah Penghentian Penyidikan (SP3) Yang Diterbitkan Berdasarkan Perdamaian Antara Tersangka dan Pelapor dalam Delik Biasa - Azizul Hakiki (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2022)
The Order for Termination of Investigation or hereinafter referred to as SP3 is the authority given attributively to criminal investigators. This paper intends to provide an analysis in terms of normative law regarding the validity of the termination of an investigation carried out based on reconciliation between the suspect and the complainant in the case of ordinary offenses. Research is a main means in developing a science and technology with the aim of revealing the existence of a truth both systematically, methodologically, and consistently through the research process as well as conducting analysis and construction of the data that has been processed and then concluded. Article 109 Paragraph (2) of Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP) states that there are three conditions to stop an investigation of a criminal act. First, there is not enough evidence. Second, the act committed by the suspect is not a crime. Third, the investigation was stopped for the sake of law. The fact that the revocation of the police report resulted in the case being discontinued or terminated, as evidenced by the issuance of an Investigation Termination Order or SP3.